2015
DOI: 10.1007/s10943-015-0004-y
|View full text |Cite
|
Sign up to set email alerts
|

Simple and Multivariate Relationships Between Spiritual Intelligence with General Health and Happiness

Abstract: The present study examined simple and multivariate relationships of spiritual intelligence with general health and happiness. The employed method was descriptive and correlational. King's Spiritual Quotient scales, GHQ-28 and Oxford Happiness Inventory, are filled out by a sample consisted of 384 students, which were selected using stratified random sampling from the students of Shahid Bahonar University of Kerman. Data are subjected to descriptive and inferential statistics including correlations and multivar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
34
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(39 citation statements)
references
References 19 publications
(18 reference statements)
0
34
0
2
Order By: Relevance
“…In this study, there was a statistically significant difference between the score of the spiritual intelligence and happiness level; this finding is consistent with Amirian study that bivariate correlations support positive and significant predictive value of spiritual intelligence toward general health and happiness. [ 27 ] In addition, according to the results of our study, there was a significant relationship between the spiritual intelligence and happiness, so the people who have higher levels of happiness, the mean score of spiritual intelligence increased. It is consistent with the results of Bagheri's study.…”
Section: Discussionmentioning
confidence: 64%
“…In this study, there was a statistically significant difference between the score of the spiritual intelligence and happiness level; this finding is consistent with Amirian study that bivariate correlations support positive and significant predictive value of spiritual intelligence toward general health and happiness. [ 27 ] In addition, according to the results of our study, there was a significant relationship between the spiritual intelligence and happiness, so the people who have higher levels of happiness, the mean score of spiritual intelligence increased. It is consistent with the results of Bagheri's study.…”
Section: Discussionmentioning
confidence: 64%
“…Spiritual intelligence can increase the flexibility and consciousness, so that the individual can be more patient when facing problems and difficulties of life (29). In their study, Amirian et al concluded that spiritual intelligence has a positive correlation with public health, and among the components of spiritual intelligence, critical thinking has an inverse significant relationship with general health (30).…”
Section: Discussionmentioning
confidence: 99%
“…8,9 General health refers effectively to the proper functioning of people in terms of thinking, mood, and behavior as well as useful activities in society, establishing positive relationships with others, and being able to face the challenges of life. 10 General health is a required item for nurses because achieving a sense of balance in general health leads to a sense of coherence in nursing jobs 11 and it is one of the important dimensions of health that depends on how nurses interact with patients. 12 Niazi et al found a statistically significant relationship between emotional intelligence and general health in nurses.…”
Section: Introductionmentioning
confidence: 99%